New species and records of Neanurinae (Collembola: Neanuridae) from Mazandaran Province (Northeastern Iran), with a key to Iranian species of the subfamily - Yahyapour, Eliye; Shayanmehr, Masoumeh; Vafaei-Shoushtari, Reza; Arbea, Javier I. (Zootaxa, 2022)
Four new species of the subfamily Neanurinae, namely Cryptonura dohezarensis sp. nov., Cryptonura abmalensis sp. nov., Cryptonura sariensis sp. nov. and Neanura persica sp. nov. from different forests in the Northern Iranian province of Mazandaran are described and illustrated. C. dohezarensis sp. nov. is characterized by body without pigment, dorsal tubercles rounded, mandible with 3 teeth, tubercles Cl and Af on head separate, tubercles Di on Th II–III with 3 chaetae and tubercle L on Abd III with 3 chaetae; C. abmalensis sp. nov.—by body with bluish pigment, dorsal tubercles triangular, mandible with 4 teeth, tubercles Cl and Af on head fused, chaetae A on head absent, tubercles L on Abd II and III with 4 chaetae and tubercle De+Dl+L on Abd V with 5 ordinary chaetae; C. sariensis sp. nov.—by body with bluish pigment, dorsal tubercles rounded, mandible with 5 teeth, tubercles Cl and Af on head separate and a reduced dorsal chaetotaxy; N. persica sp. nov. belongs to the group of Neanura with ventral chaetae L’ on Abd V, without chaetae Ocp on the head and tubercles Di on Th I absent, and is characterized by one character unknown in other members of the genus, e.g., the fusion of cephalic tubercles Cl and Af. In addition four other taxa have been found in the same forests: Cryptonura persica Smolis et al., 2012 and three species that may represent new species but there is insufficient material available to prepare full descriptions (one species in the genus Cryptonura, one in Vitronura and one in Endonura). An identification key of the genus and species of Neanurinae recorded so far from Iran is given.